Know your cholesterol: population screening - Laemmle, P; Unger, L; McCray, C; Geisler, M; Chalin, M; Hardy, R I; Glueck, C J (The Journal of laboratory and clinical medicine, 1988)
To facilitate the goal that all adult Americans know their total serum cholesterol levels, our specific aim was to evaluate the effectiveness, practicality, and cost of total cholesterol sampling in nonfasting self-referred subjects with use of venous blood and mailed results (n = 3844), and to compare these results with capillary blood total cholesterol levels (n = 1167), with immediate turnaround. We used consensus cut points of total cholesterol levels greater than 200, greater than 220, and greater than 240 mg/dl for moderate risk of coronary heart disease and greater than 220, greater than 240, and greater than 260 for high risk for aged 20 through 29, 30 through 39, and greater than 40 years. Total cholesterol level was in the moderate- or high-risk range in 45% and 37% of the venous and capillary cohorts, respectively. Median venous and capillary total cholesterol values were approximately 20 and 10 mg/dl greater than the total cholesterol values in the Lipid Research Clinics Prevalence Study, a difference contributed to by nonfasting versus fasting conditions, use of serum versus plasma, and self-referral bias for subjects with a family history of premature coronary heart disease. The cost per subject in the venous and capillary studies was $5.09 and $7.12 respectively, and $11.40 and $ 18.63 for each subject in the moderate- to high-risk range. Resampling with the subject fasting and follow-up were stressed, and were made available for moderate- and high-risk subjects.